TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI DENGAN VULVA HYGIENE PADA REMAJA PUTRI - Pusungunaung, Feybrianty; Ake, Julianus; Tiwatu, Filia (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Background: Reproductive health is often neglected by women. One of the factors is the lack of knowledge and awareness of reproductive health. Keeping the vulva clean is very important so that it is kept away from hazards that might interfere with reproductive health. Care for the outer genitalia (vulva) or commonly referred to as vulva hygiene is a behavior in which individuals can maintain the cleanliness of the outer genitals so that they remain clean and healthy and prevent the possibility of infection. Objective: To determine the relationship between the level of reproductive health knowledge and vulva hygiene in class XI adolescent girls at SMA N 1 Beo, Beo District, Talaud Islands Regency Method: This study uses a descriptive analytic/quantitative design with a cross sectional approach. The population is all girl’s class XI. The number of samples is 74 respondents determined by total sampling technique. Results: This study used the Fisher Exact Test. The results showed that there was a significant relationship between the level of reproductive health knowledge and vulva hygiene in class XI female adolescents at SMA N 1 Beo, Beo District, Talaud Islands Regency, with a p-value of 0.042 <α = 0.07. Conclusions: From the results of the study, it was found that there was a significant relationship between the level of reproductive health knowledge and vulva hygiene in class XI female adolescents at SMA N 1 Beo, Beo District, Talaud Islands Regency.